1997
DOI: 10.1007/s001250050708
|View full text |Cite
|
Sign up to set email alerts
|

Association of diabetic neuropathy with Na/K ATPase gene polymorphism

Abstract: Neuropathy is a leading cause of disability in diabetes mellitus. Unlike diabetic retinopathy which is an almost constant long-term complication, diabetic neuropathy occurs in only 50 % of cases [1]. This phenomenon is comparable to that observed with diabetic nephropathy [2] which has been associated with genetic susceptibility [3,4]. A number of facts suggest Diabetologia (1997) 40: 506-511 Association of diabetic neuropathy with Na/K ATPase gene polymorphism Summary Diabetes mellitus induces a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 28 publications
(32 reference statements)
2
33
0
1
Order By: Relevance
“…In this study, we confirmed our previous finding [3,4,5,6] that diabetic neuropathy is associated with lower erythrocyte Na/K ATPase in Type I diabetic patients. The same finding was also observed in Type II diabetic patients.…”
Section: ±1supporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we confirmed our previous finding [3,4,5,6] that diabetic neuropathy is associated with lower erythrocyte Na/K ATPase in Type I diabetic patients. The same finding was also observed in Type II diabetic patients.…”
Section: ±1supporting
confidence: 92%
“…As we showed in previous studies [3,5,6], erythrocyte Na/K ATPase activity is lower in Type I diabetic patients than in control subjects. In the entire group of Type II diabetic patients, mean enzymatic activity was similar to that of control subjects.…”
Section: Discussionsupporting
confidence: 65%
“…In this context, reduced/impaired Na + /K + -ATPase activity and increased aldose reductase activity may play a supplementary role [97][98][99][100]. Na + /K + -ATPase may be influenced by metabolic control and C-peptide secretion [101].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…These isoforms are coded by different genes due to tissue type and developmental stages. α 1 isoform is commonly exist in peripheral nerves and erythrocytes [3].…”
Section: öZetmentioning
confidence: 99%